2013
DOI: 10.1186/1477-7819-11-259
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of hepatocellular carcinoma with tumor thrombi in the inferior vena cava or right atrium

Abstract: BackgroundThe prognosis for advanced hepatocellular carcinoma (HCC) with tumor thrombi in the inferior vena cava (IVC) or right atrium (RA) is poor, and there is no established effective treatment for this condition. Thus study aimed to evaluate the efficacy of surgical resection and prognosis after surgery for such cases.MethodsBetween January 1990 and December 2012, 891 patients underwent hepatectomy for HCC at our institution. Of these, 13 patients (1.5%) diagnosed with advanced HCC with tumor thrombi in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(106 citation statements)
references
References 33 publications
4
101
1
Order By: Relevance
“…Due to the paucity of data regarding the best management of HCC patients with HVTT or IVCTT, therapeutic options for this subgroup of patients are controversial. Currently, surgical resection of the primary tumor and the tumor thrombus and TACE with or without conformal radiotherapy have been reported, but there is no current credible evidence suggesting that these therapies offer benefits to patients, because all previous studies were either case reports or had a non‐control design . To our knowledge, this is the first large case series study to compare treatment outcomes among HCC patients with HVTT or IVCTT who were treated with LR or TACE using PSM analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the paucity of data regarding the best management of HCC patients with HVTT or IVCTT, therapeutic options for this subgroup of patients are controversial. Currently, surgical resection of the primary tumor and the tumor thrombus and TACE with or without conformal radiotherapy have been reported, but there is no current credible evidence suggesting that these therapies offer benefits to patients, because all previous studies were either case reports or had a non‐control design . To our knowledge, this is the first large case series study to compare treatment outcomes among HCC patients with HVTT or IVCTT who were treated with LR or TACE using PSM analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The resection of HCC with tumor thrombus extending into the right atrium is limited to case reports. Early recurrence within 6 months occurred in almost all patients, even if the patients underwent complete tumor resection [44]. However, surgical resection of metastasis to the right atrium may relieve associated symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Kokudo and colleagues 12 , in an analysis of data from the Liver Cancer Study Group of Japan database, reported excellent patient outcomes for patients with HCC and IVC TT who received systemic chemotherapy or HAIC, with a median OS of 15⋅4 months. In contrast, for surgical resection, promising median OS results in these patients have been reported as 16⋅7-30⋅8 months 8,12,13,15 . These reports imply that resection should be incorporated in the multidisciplinary treatment of this advanced disease.…”
Section: Discussionmentioning
confidence: 97%